Implementasi prinsip prinsip manajemen Sarana dan Prasarana di sekolah luar biasa ABC Yayasan insan sejahtera Tasikmalaya - Silvy nuril amini; Halimah, Ai Hilyatul; R.B, Zahra; Rohman, Ujang Abdul; Fadhilah, Agim; Royani, Ade; Padilah, Dapa (Institut Nahdlatul Ulama Tasikmalaya, 2024)
Whether we realize it or not, school facilities and infrastructure (sarpras) greatly support the implementation of education. The existing infrastructure in schools needs to be managed so that its use is optimal and really supports learning. This study aims to analyze the application of the principles of management of educational facilities and infrastructure (sarpras) in SLB ABC Tasikmalaya. The principles of sarpras management that become the reference are the principles of suitability, efficiency, administration, responsibility, and cohesiveness according to Mulyasa. This research uses a qualitative approach with data collection techniques in the form of interviews and observations. The results showed that the management of sarpras in SLB ABC has not fully met the principles of sarpras management. First, the principle of conformity to needs has not been fulfilled because the amount of sarpras still does not meet the ideal standard. Secondly, the principle of efficiency has only been partially fulfilled because a detailed analysis of sarpras needs has not been completed. Third, the principle of administration has been applied with the inventory of sarpras, but the constraint is the lack of specialized human resources for management. Fourth, the principle of responsibility has been shared among school elements, but there is no written job description to ensure accountability. Finally, the principle of cohesiveness has been applied through cooperation between school elements, but coordination and program evaluation have not been regularly scheduled. This study recommends improvements in the aspects of the suitability of the amount of sarpras, planning and needs analysis, increasing the capacity of human resources managers, clarifying written responsibilities, and more structured coordination and evaluation to optimize the management of sarpras in SLB ABC.